Exploring the mechanisms of sexual dimorphism in oxygen delivery-to-utilization matching in skeletal muscle - Craig, Jesse Charles (Kansas State University, 2018)
The onset of skeletal muscle contractions induces rapid and robust increases in metabolic rate (V̇O₂) and blood flow (Q̇) in order to supply the energetic demands of the muscle. In young healthy populations, these variables increase proportionally to maintain oxygen flux into the myocyte for both sexes. However, while the resultant changes in V̇O₂ and Q̇ conflate to establish adequate driving pressures of oxygen (PO₂), it appears that the underlying control processes express distinct sexual dimorphism. Estrogen is crucial for cardiovascular control for young women through its relationship with nitric oxide (NO) and results in lower blood pressure and risk of cardiovascular disease for women. However, in post-menopausal women and some disease states, such as heart failure (HF), these protections are lost due to reductions in estrogen and NO bioavailability which causes women to catch and surpass men in rates of hypertension and cardiovascular disease. The purpose of this dissertation is to explore the mechanisms responsible for establishing the oxygen delivery-to-utilization matching (Q̇O₂/V̇O₂) necessary for skeletal muscle contractions in health and disease. In the first investigation (Chapter 1), we explored the effect of altered NO bioavailability on spinotrapezius muscle interstitial space PO₂ (PO₂is; determined by Q̇O₂/V̇O₂) of healthy male and female rats. We show that both sexes regulate PO₂is to similar levels at rest and during skeletal muscle contractions. However, modulating NO bioavailability exposes sex differences in this regulation with females having greater reliance on basal NO bioavailability and males having greater responsiveness to exogenous NO. In the second investigation (Chapter 2), we sought to determine whether measures of central and peripheral function in HF rats predicted exercise tolerance (as critical speed (CS)). We showed for the first time, that CS can be resolved in HF animals and that decrements in central cardiac (echocardiography) and peripheral skeletal muscle function (PO₂is) predicted CS. Building upon these findings, the third investigation (Chapter 3) aimed to determine if the sex differences in the control of PO₂is seen in healthy rats translated to greater deficits in HF for females. Furthermore, this investigation sought to determine if five days of dietary nitrate supplementation (an exogenous NO source) would raise PO₂is in HF rats, with a greater effect seen in females. We revealed that HF reduces PO₂is at rest and during skeletal muscle contractions and this negative effect is exacerbated for females. However, elevating NO bioavailability with dietary nitrate increases resting PO₂is and alters the dynamic response during contractions with females potentially being more responsive than males. The results herein reveal the importance of NO in the control of Q̇O₂/V̇O₂ in health. The onset of HF results in deleterious declines in exercise tolerance, which are mediated through reductions in central and peripheral function, due, in part, to attenuated NO bioavailability. This creates intensified Q̇O₂/V̇O₂ dysfunction in females with HF; however, this can potentially be countered with dietary supplementation of inorganic nitrate. Altogether, the present dissertation suggests that targeting NO bioavailability, particularly in female HF patients, could be a beneficial non-pharmaceutical therapeutic strategy.
Keywords: Oxygen delivery; Sex; Chronic heart failure; Exercise tolerance; Dietary nitrate